Riesgos laborales en las actividades de los trabajadores del departamento de higiene ambiental y desechos sólidos- GAD Pedernales - Demera Zambrano, Jackson Andrés (2024)
Occupational risks and occupational diseases are increasingly worrying many workers globally, with solid waste collection being one of the ten most dangerous occupations in the world due to the precarious conditions to which workers are exposed. For this research, the 22-worker sample was applied to the IPER Matrix, which allowed to identify and assess the hazards and risks to which solid waste collection workers from the Environmental Hygiene and Solid Waste Department at the Pedernales GAD are exposed during their daily work shifts and the procedures were specified that support the verification of the measures adopted. As a result, through the IPER Matrix, 9 present hazards were identified, with 100% of workers represented by males with ages ranging from 20 to 60 years old, and fractures, sprains, and twists being the most common accidents. Of the nine risks evaluated, five were weighted as acceptable, while the remaining 4 were considered important, with significant risks such as fractures, musculoskeletal injuries, deafness, sunburn, or heat stroke standing out. Based on this, a labor risk prevention program was developed that aims to apply actions that lead to the prevention and/or mitigation of the risks already identified, under guidelines that promote their execution, compliance, and continuity to reduce labor risks.